Droplet spectrum at different vapour pressure deficits - Maciel, Christiam Felipe; Teixeira, Mauri; Fernandes, Haroldo; Zolnier, Sérgio; Cecon, Paulo (Revista Ciência Agronômica, 2015)
An efficient pesticides spraying depends a lot in psychrometric conditions, mainly if it is using fine droplets, once climatic conditions may cause droplets evaporation and consequent financial loss to the farmer. Thus, the aim of this work was to determine the droplet spectrum depending on the vapour pressure deficits. The work was carried out inside of a climate chamber to obtain the vapour pressure deficits (VPDair). The laser particle analyzer, model Spraytech, was used to determine the droplet spectrum, and the experiment was conducted in factorial scheme 5 x 20, consisted of five working pressures (100; 200; 300; 400 and 500 kPa) and twenty VPDair (2.3; 3.2; 4.2; 5.6; 7.0; 7.4; 9.5; 11.7; 12.7; 15.8; 16.4; 16.9; 21.2; 22.1; 22.2; 28.1; 29.7; 36.9 39.4 e 51.6 hPa), in completely randomized design with five replications. There is influence of VPDair on droplet spectrum behavior. Increasing the VPDair reduces the percentage of sprayed volume comprised by droplets with diameter between 100 and 200 µm, between 200 and 300 µm, between 300 and 400 µm, between 400 and 500 µm and between 500 and 600 µm. Increasing VPDair increases the VMD, Dv90, SPAN and the percentage of sprayed volume comprised by droplets larger than 600 µm.